2011
DOI: 10.3109/09638288.2011.619622
|View full text |Cite
|
Sign up to set email alerts
|

Falls efficacy among stroke survivors living in the community

Abstract: Purpose. The study focused on the falls efficacy of stroke survivors in the community and its association with the related factors. Method. The study was conducted through a cross-sectional design in the community setting. One hundred and seven stroke survivors were recruited. Falls efficacy was measured by the 7-item Falls Efficacy Scale International version, where the higher mean score showed more concern about falling in daily life. Results. Activities of daily living (ADLs) dependency levels, including mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A higher total score indicates a greater concern for falling. The FES‐I has been tested in persons with stroke [16]. A cut‐off score of 27 points on the 16‐item FES‐I was used to differentiate high concern for falling from low concern [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher total score indicates a greater concern for falling. The FES‐I has been tested in persons with stroke [16]. A cut‐off score of 27 points on the 16‐item FES‐I was used to differentiate high concern for falling from low concern [26].…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between fear of falling and falls appears controversial. Previous studies have demonstrated that patients with a history of falling often reported greater concern for falling [5,15,16]. However, Friedman et al [17] showed that fall status at the acute phase did not predict development of fear of falling measured at 20 months [17].…”
Section: Introductionmentioning
confidence: 98%
“…Stroke survivors have been plagued with adverse outcomes after returning home, including falls, 4 hospitalizations, 5 or physical function decline. 6 Navigating these adverse outcomes has burdened their family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Stroke is a leading cause of long-term disability and reduces mobility in more than half of stroke survivors ≥65 years of age. 2 Stroke survivors with limitations in activities of daily living (ADL), such as going outside, moving around the house, getting in and out of bed, toileting, and dressing, are at a greater risk of experiencing adverse outcomes, 3 including falls, 4 hospitalizations, 5 and physical function decline, 6 relative to those without ADL limitations. These findings agree with studies documenting the positive relationship between poor physical function/ADL limitations and adverse outcomes in older adults.…”
mentioning
confidence: 99%
“…However, Wei et al37 reported that the occurrence of falls is linearly associated with patients' ADL evaluated with FIM, and when the FIM score increased by 1 point, the fall risk decreased by 10%. Tsai et al38 also suggested that moderate and severe ADL dependency has a higher fall risk than ADL independent patients who have suffered a stroke in the community. These differences may be due to the different study populations and settings or the different ADL assessment scales used.…”
Section: Discussionmentioning
confidence: 99%